1998
DOI: 10.1093/humrep/13.10.2962
|View full text |Cite
|
Sign up to set email alerts
|

An effective regimen for early medical abortion: a report of 2000 consecutive cases

Abstract: A combination of the anti-progesterone mifepristone and gemeprost provides an effective non-surgical method for the induction of abortion at gestations up to 63 days, achieving complete abortion rates of over 95%. We report our experience with an alternate regimen, comprising a reduced dose of mifepristone in combination with vaginal misoprostol. A consecutive series of 2000 women requesting early medical abortion at gestations up to 63 days was studied retrospectively. Each woman received mifepristone 200 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
105
1
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(118 citation statements)
references
References 8 publications
10
105
1
2
Order By: Relevance
“…13 In present study maximum patients had amenorrhea <40 days in group A and maximum patients had amenorrhea 56-59 days in group B.…”
supporting
confidence: 47%
“…13 In present study maximum patients had amenorrhea <40 days in group A and maximum patients had amenorrhea 56-59 days in group B.…”
supporting
confidence: 47%
“…In clinical trials, a combination of mifepristone and misoprostol for early first trimester termination of pregnancy has a high completion rate of 96-98% up to 63 days of pregnancy. [4][5][6] However, mifepristone is not available in any Latin American or Caribbean country. Thus, misoprostol alone, or a combination of methotrexate and misoprostol, 7 are medical alternatives for safe, early abortion.…”
mentioning
confidence: 99%
“…7,8 WHO task force in 1993 has suggested that for termination of early pregnancy, a single dose of 200mg of mifepristone is as effective as 600mg, when used in combination with PGE1. 9 Most studies using PGE1 alone for medical management of delayed miscarriage have a success rate of 13-83%, de Jonge et al 10 Overall complete abortion was 97.6% in a study by PW Ashok et al 11 Chung et al, reported an overall efficacy rate of 70.6%. 12 Demetrolis et al showed a failure rate of using PGE1 alone to be 23.1%.…”
Section: Discussionmentioning
confidence: 99%